Case Report: Lesson Learned from Rehabilitation Medicine Point of View for an Elderly with Normal Pressure Hydrocephalus - Defi, Irma Ruslina; Andre, Andre; Sastradimadja, Sunaryo Barki; Faried, Ahmad (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Normal pressure hydrocephalus (NPH) is characterized by an abnormal buildup of cerebrospinal fluid in the ventricles or cavities of the brain. The objective of the case report was to define the importance of physical medicine and rehabilitation intervention as an approach for an elderly patient with NPH. CASE REPORT: A 75-year-old woman presented with a balance and gait disturbance after injury from a motor vehicle accident. The patient experience Hakim’s triad (gait disturbance, urinary frequency, and mild cognitive impairment), and her computed tomography scan of the head revealed ventriculomegaly, multiple lacunar infarctions on the paraventricle, and cerebral atrophy, which could indicate NPH. Balance and gait training, cardiopulmonary training, and environment modification were interventions from physical medicine and rehabilitation provided to this patient. CONCLUSION: An elderly patient with NPH should receive physical medicine and rehabilitation intervention to prevent falls, improve functional ability, and improve quality of life.